Veiled Exploitation: The Maintenance of Power through False Consciousness in The Netflix Series Arcane - Ananda Lukmanul Hakim; Inayatul Chusna (Journal of Language and Literature, 2024)
The focus of this research is to identify and reveal how false consciousness is created and utilized to retain the authority of the industrialist Silco in the Netflix series Arcane. This research aims to show how false consciousness is through the creation of class consciousness, and how it is spread and maintained through state apparatuses and commodity fetishism as a method of exploitation to maintain his authority and status as a leader in Zaun. In this research, the Marxist theory of ideology and state apparatuses by Louis Althusser and commodity fetishism by Karl Marx were employed to answer the research questions. The research used a qualitative method of content analysis. The data is collected and identified by watching the series, where the relevant data is collected from visuals, activities, and dialogues within the series so that it can be analyzed further. Based on the data analysis, the series Arcane depicts false consciousness as a method to exploit the people from the proletariat and bourgeois classes to benefit certain people or groups. Silco creates and maintains false consciousness by utilizing state apparatuses such as ideological state apparatus and repressive state apparatus through ideology. Silco also utilizes commodity fetishism from Shimmer as a way to control the people through false consciousness. As a result, Silco managed to maintain his power as a leader in Zaun, which reveals how false consciousness can be utilized to benefit a certain people, group, or classes to maintain their power within society.